The influence of transformational leadership, organizational culture, and employee engagement on turnover intention - Rhian Indradewa; Santiajie Santiajie (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
A high desire to stop is a sign of a fundamental problem in a company. For the desire to quit employees to decrease, the company needs to consider some elements that impact the intention to quit. This study analysed the influence of transformational leadership, organizational culture, and employee engagement on turnover intention: job satisfaction as an intervening in a hospital. The samples included were 221 employees using the saturated sampling method. Questionnaires are used to collect data. SEMPLS is used as an analysis tool. According to the findings of this study, the variables transformational leadership, organizational culture, employee engagement, and job satisfaction significantly influence turnover intention. The theoretical insight provided by this study is the assumption that transformational leadership, organizational culture, employee engagement and job satisfaction can reduce turnover intention. For further research, it is suggested to examine other hospital that face the same problem which may produce different findings; conduct research on relatively similar objects, such as leasing which also faces the same problem, and add the concept of transformational leadership, organizational culture, and employee engagement, turnover intention, job satisfaction and others for further research.